Studi Perbandingan Penanganan Pengungsi Luar Negeri Di Indonesia, Australia, Dan Thailand - Mohamad Hidayat Muhtar; Zamroni Abdussamad; Zainal Abdul Aziz Hadju (Jurnal Hukum IUS QUIA IUSTUM, 2023)
Indonesia specifically addresses the refugee issues in Presidential Regulation No. 125 of 2016 on the Handling of Foreign Refugees. The handling of refugee status in Indonesia is handed over to UNHCR considering that Indonesia is not a party to the 1951 Refugee Convention or the 1967 Protocol. Besides Indonesia, Australia and Thailand are also not parties to the convention. Therefore it is important to see a comparative study of policies between countries. This study also aims to find out whether Presidential Decree No. 125 of 2016 can resolve the problem of refugees in Indonesia and what is the policy comparison between Indonesia, Australia and Thailand. The research method used is normative legal research with a statutory approach. The results of the study concluded that Presidential Decree No. 125 of 2016 has adequately accommodated arrangements for overseas refugees, but there are still several provisions that have multiple interpretations, such as arrangements regarding "foreigners", Rudenim arrangements, and the principle of "local integration" that has not been regulated. The implementation in Australia is firmer compared to Thailand and Indonesia. Australia itself emphasizes forced repatriation if it is detected as threatening the country's sovereignty. Meanwhile, Thailand provides access to foreign refugees to submit applications so they can live and settle.Key Words: Presidential decree 125 Year 2016, Refugees, 1951 Convention, 1967 Protocol AbstrakIndonesia secara khusus mengatur masalah pengungsi dalam Peraturan Presiden No. 125 Tahun 2016 tentang Penanganan Pengungsi Luar Negeri. Penanganan status pengungsi di Indonesia diserahkan kepada UNHCR mengingat Indonesia bukan negara pihak Konvensi Pengungsi 1951 atau Protokol 1967. Selain Indonesia, Australia dan Thailand juga bukan negara pihak konvensi. Oleh karena itu penting untuk melihat studi perbandingan kebijakan antar negara. Penelitian ini juga bertujuan untuk mengetahui apakah Perpres No. 125 Tahun 2016 dapat menyelesaikan masalah pengungsi di Indonesia dan bagaimana perbandingan kebijakan antara Indonesia, Australia dan Thailand. Adapun metode penelitian yang digunakan, yaitu penelian hukum normatif dengan pendekatan perundang-undangan. Hasil penelitian menyimpulkan bahwa Perpres No. 125 Tahun 2016, telah cukup mengakomodasi pengaturan pengungsi luar negeri, akan tetapi masih terdapat beberapa ketentuan yang multitafsir, seperti pengaturan tentang “orang asing”, pengaturan Rundenim, dan belum diaturnya mengenai prinsip “integrasi lokal”. Adapun implementasi di negara Australia lebih tegas dibandingkan dengan Thailand dan Indonesia. Asutralia sendiri menegaskan pemulangan paksa jika terdeteksi mengancam kedaulatan negara. Sedangkan Thailand memberikan akses kepada pengungsi luar negeri untuk mengajukan permohonan agar dapat tinggal dan menetap.Kata-kata Kunci: Perpres 125 Tahun 2016; Pengungsi; Konvensi 1951; Protokol 1967